Stress, physical activity, and mindfulness practices among youth amidst COVID-19 - El Hajj, A.; Noulhiane, M.; Andrieu, B.; Heutte, Natacha; Sirost, O. (Frontiers in Sports and Active Living, 2024)
Introduction The COVID-19 pandemic has exacerbated stress and anxiety among young people, particularly university students, impacting their mental well-being and daily life. Given the rise in social isolation and economic uncertainty, the adoption of mindfulness practices such as sophrology, meditation, and yoga becomes essential for improving their mental health. This study aims to evaluate the impact of these practices on stress levels and their effect on engagement in physical activities among youths. Method This study employed a mixed methods design to assess the impact of different wellness and mindfulness practices on stress levels and physical activity (PA) engagement among university students. Quantitative data were gathered electronically from 218 students at the University of Rouen and the university of Paris-Cité through validated questionnaires, including custom tools on sports and mindfulness practices and the Perceived Stress Scale (PSS). The sample consisted mainly of young adults aged 18 to 35, with a majority of 170 female and 48 male participants. Qualitative insights were gathered through semi-structured interviews with three directors of the university's sports and physical activities department (SUAPS), as well as four wellness program instructors. Data analysis involved statistical techniques using Statistical Analysis System (SAS) software for quantitative data, while qualitative data were analyzed thematically using Sphinx software, a tool for textual analysis. Ethical approval for the study was obtained, and confidentiality of all participants was maintained throughout the research. Results and conclusion The COVID-19 pandemic had significant effects on French university students’ PA, mental health, and stress levels. Lockdowns led to a decline in sports practices for many, while others adapted by increasing their engagement in fitness and wellness practices. The majority of participants (64.68%) reported moderate levels of stress. A significant correlation was found between motivations for mental health support and stress management, and higher levels of stress (p = 0.0000 and p = 0.0024, respectively). Regular participation in wellness activities was associated with lower stress (p = 0.0193). The findings reinforce the idea that incorporating wellness practices into educational environments can strengthen students’ mental resilience and overall well-being, equipping them with essential tools to effectively cope with future stressors.